The effect of a training program in developing the dialogue skill of kindergarten children according to gender (Journal of the College of Basic Education, 2022)
The current study aimed at developing (dialogue skill) and aimed at:1- Identifying the level of dialogue skill among the respondents according to gender (male, female).2- Detecting the effectiveness of the impact of a training program in developing the dialogue skill according to gender.To achieve the objectives, the researcher did the following:1- Building a measure to follow the steps to be implemented and verified from its psychometric characteristics. The (dialogue scale) consisted of (14) items. The researcher verified the availability of the psychometric properties of the items (discriminatory power, internal consistency, factorial saturation), and it was acceptable in the light of its statistical treatments as well as The characteristics of the tool, including virtual validity, constructive validity, and the stability value using (K-R20) method, amounted to (0.748).